The many forms of a pleomorphic bacterial pathogen—the developmental network of Legionella pneumophila - Robertson, Peter; Abdelhady, Hany; Garduño, Rafael A. (Frontiers in Microbiology, 2014)
Legionella pneumophila is a natural intracellular bacterial parasite of free-living freshwater protozoa and an accidental human pathogen that causes Legionnaires’ disease. L. pneumophila differentiates, and does it in style. Recent experimental data on L. pneumophila’s differentiation point at the existence of a complex network that involves many developmental forms. We intend readers to: (i) understand the biological relevance of L. pneumophila’s forms found in freshwater and their potential to transmit Legionnaires’ disease, and (ii) learn that the common depiction of L. pneumophila’s differentiation as a biphasic developmental cycle that alternates between a replicative and a transmissive form is but an oversimplification of the actual process. Our specific objectives are to provide updates on the molecular factors that regulate L. pneumophila’s differentiation (section 2), and describe the developmental network of L. pneumophila (section 3), which for clarity’s sake we have dissected into five separate developmental cycles. Finally, since each developmental form seems to contribute differently to the human pathogenic process and the transmission of Legionnaires’ disease, readers are presented with a challenge to develop novel methods to detect the various L. pneumophila forms present in water (section 4), as a means to improve our assessment of risk and more effectively prevent legionellosis outbreaks.